Analisis Yuridis Hak Asuh Anak (Hadhanah) sebagai Objek Pembuktian dalam Hukum Perdata serta Akibat Hukumnya dalam Perspektif Kepentingan Terbaik Anak - Arlinda Aulia Putri; Diana Tantri Cahyaningsih (Indonesian Journal of Social Sciences and Humanities, 2026)
Child custody (hadhanah) in civil cases, particularly after divorce, is not merely viewed as a right of the parents, but rather as a right of the child that must be legally protected. This protection is essential as it concerns the continuity of a child’s physical and psychological development amid changes in family structure. This study aims to analyze the position of hadhanah as an object of proof in civil law and to examine the legal implications from the perspective of the best interest of the child. The method used is normative legal research with a statutory approach. The findings show that hadhanah is a crucial object of proof in judicial decisions, where evidence such as witness testimonies, documents, and court facts form the basis for assessing the suitability of custody. This protection is important as it relates to the sustainability of a child’s growth and development, both physically and psychologically, in the midst of changing family structures. Its legal consequences do not only affect the determination of custody rights, but also the legal responsibilities of parents, including obligations for care, education, and child protection. Therefore, the application of the principle of the best interest of the child must be a primary consideration in every court decision.